2019
DOI: 10.1016/j.drugalcdep.2018.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute treatments with the serotonin 2A antagonist M100907 alone or in combination with the serotonin 2C agonist WAY163909 on methamphetamine self-administration in rhesus monkeys

Abstract: Background: Serotonin 5-HT2A receptor antagonists and 5-HT2C receptors agonists have been proposed as important candidates for the development of pharmacotherapies for psychostimulant abuse, with evidence suggesting that those receptors may act together to control behavior. However, the role of 5-HT2A receptors on the reinforcing effects of psychostimulant drugs has not been fully elucidated. Methods: In the present study, we investigated the effects of the selective 5HT2A receptor antagonist M100907 alone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…29 In addition, WAY-163909 has been shown to have potential uses in anti-obesity drugs and the treatment of certain drug addictions. 30…”
Section: Transition Metal Complex-catalysed Asymmetric Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In addition, WAY-163909 has been shown to have potential uses in anti-obesity drugs and the treatment of certain drug addictions. 30…”
Section: Transition Metal Complex-catalysed Asymmetric Hydrogenationmentioning
confidence: 99%
“…29 In addition, WAY-163909 has been shown to have potential uses in anti-obesity drugs and the treatment of certain drug addictions. 30 To accelerate the development of the indoline moiety in drugs, more methods are required to produce their substituted cores in enantiomerically pure forms. Indoles are a challen-ging structure for EH to afford indolines.…”
Section: Introductionmentioning
confidence: 99%
“…5-Hydroxytryptamine (serotonin) 2A receptors regulate neuropsychological functions ( Pogorelov et al, 2017 ; Mora et al, 2018 ; Odabas-Geldiay et al, 2019 ) and have been shown to play a role in a number of neurological disorders, including Alzheimer’s disease ( Ballard et al, 2018 ), Parkinson’s disease ( Cummings et al, 2014 ; Ohno et al, 2015 ), obsessive–compulsive disorder ( El Mansari and Blier, 2006 ; Steeves and Fox, 2008 ; Simpson et al, 2011 ; Sinopoli et al, 2017 ), schizophrenia ( Girgis et al, 2020 ), autism spectrum disorder ( Chen et al, 2013 ), depression ( Underwood et al, 2018 ), anxiety ( Weisstaub et al, 2006 ), insomnia ( Teegarden et al, 2008 ), and obesity ( Morris, 2017 ). The 5-HT2AR antagonist volinanserin or MDL100907 (Aventis Pharmaceuticals) has been used to treat neuropsychological dysfunctions in drug-addicted patients ( Cunningham et al, 2013 ), and a synergism between the 5-HT2AR and 5-HT2CR affects the severity of addictive behaviors ( Cunningham et al, 2013 ; Perez-Aguilar et al, 2014 ; Prabhakaran et al, 2015 ; Felsing et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%